Nurses’ knowledge, attitudes, and behaviors of inadvertent perioperative hypothermia prevention in China: a multicenter, cross-sectional study - Lei Yang; Wenjuan Tang; Qingqing Du; Yingmin Liu; Zhen Wang; Xia Yang (BMC Pediatrics)
Abstract Background Inadvertent perioperative hypothermia (IPH) is a clinical phenomenon in which patient’s core body temperature is below 36℃ due to non-medical purposes during the perioperative period. Children are more s usceptible to hypothermia due to their significantly higher surface area-to-body weight ratio compared to adults, the immaturity of their thermoregulatory centers, and the thinness of their subcutaneous fat insulation layer. Perioperative nursing is an essential component of the multiprofessional management of surgical patients. Since nurses are the primary caregivers and monitors of patients during perioperative process, a better understanding of nurses’ knowledge, attitudes and behaviors regarding IPH prevention is critical to improving patient outcomes. Consequently, a multicenter cross-sectional study was carried out to investigate the current situation of anesthesia and operating room nurses in China, as well as the prevention of inadvertent perioperative hypothermia and its influencing factors. Methods In this study, 292 nurses from 7 children’s specialized hospitals in 4 provinces (Hunan, Anhui, Zhejiang, and Shanghai) in the southern, northern, and central regions of mainland China participated in two-stage purposive and convenience mixed sample technique. General demographic information questionnaire, the knowledge, attitudes, and behaviors questionnaire, and the self-efficacy scale were used for data collection. Descriptive analysis, univariate analysis, correlation analysis, and multiple linear regression analysis were used for data analysis. Results The results indicated that mean (SD) score of knowledge, attitudes, and behaviors scales were 15.59 (3.28), 47.02 (8.05), and 52.48 (6.35), respectively. Results of multiple linear regression analysis showed that educational level (t = 2.278, P < 0.05), No. of IPH training (t = 3.408, P < 0.01) and whether there was a perioperative insulation process (t=-3.091, P < 0.01) were risk factors for knowledge; No. of IPH training (t = 3.175 P < 0.01) was risk factor for attitudes; No. of IPH training (t = 2.476, P < 0.05), whether there was a perioperative insulation process (t=-6.612, P < 0.01) and self-efficacy (t = 2.851, P < 0.01) were risk factors for behaviors. Correlation analysis displayed self-efficacy was positively related to knowledge (r = 0.137, P < 0.05), attitudes (r = 0.115, P < 0.05), and behaviors (r = 0.258, P < 0.01); knowledge was also positively correlated with attitudes (r = 0.262, P < 0.01) and behaviors (r = 0.322, P < 0.01); attitudes were positively related to behaviors (r = 0.153, P < 0.01). Conclusions To improve knowledge, attitudes, and behaviors of IPH prevention among operating room nurses and anesthesia nurses in children’s specialized hospitals, nursing managers should increase the frequency of IPH training and develop standardized perioperative insulation process. Nurses should also enhance their theoretical knowledge learning, improve educational level and self-efficacy.